2013
DOI: 10.1242/dev.094599
|View full text |Cite
|
Sign up to set email alerts
|

CAF-1 promotes Notch signaling through epigenetic control of target gene expression during Drosophila development

Abstract: SUMMARYThe histone chaperone CAF-1 is known for its role in DNA replication-coupled histone deposition. However, loss of function causes lethality only in higher multicellular organisms such as mice and flies, but not in unicellular organisms such as yeasts, suggesting that CAF-1 has other important functions than histone deposition during animal development. Emerging evidence indicates that CAF-1 also has a role in higher order chromatin organization and heterochromatin-mediated gene expression; it remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
2
35
1
Order By: Relevance
“…The regulation of this pathway occurs at different levels and is especially well-characterized for the stages before nuclear entry of NICD (Andersson et al, 2011;Guruharsha et al, 2012;Tien et al, 2009). Recent findings from our laboratory and others have shown that Notch signaling can be regulated epigenetically by the CAF1 chromatin chaperone complex or by the SWI/SNF chromatin remodeling complex in different tissues (Yu et al, 2013;Zeng et al, 2013). Our studies address how the Su(H)-NICD-Mam transcriptional complex of the Notch pathway interacts with the general transcription factor complexes to initiate expression of Notch target genes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The regulation of this pathway occurs at different levels and is especially well-characterized for the stages before nuclear entry of NICD (Andersson et al, 2011;Guruharsha et al, 2012;Tien et al, 2009). Recent findings from our laboratory and others have shown that Notch signaling can be regulated epigenetically by the CAF1 chromatin chaperone complex or by the SWI/SNF chromatin remodeling complex in different tissues (Yu et al, 2013;Zeng et al, 2013). Our studies address how the Su(H)-NICD-Mam transcriptional complex of the Notch pathway interacts with the general transcription factor complexes to initiate expression of Notch target genes.…”
Section: Discussionmentioning
confidence: 99%
“…These genetic experiments suggest that e(y)1 functionally interacts with the Notch pathway during Drosophila wing development. The Notch signaling pathway is delicately regulated at multiple levels, including ligand and receptor post-translational modification, endocytosis and vesicle trafficking, and epigenetic regulation of target gene expression (Fischer et al, 2006;Fortini and Bilder, 2009;Tien et al, 2009;Yu et al, 2013;Zeng et al, 2013). Interaction between Notch ligand and receptor induces two consecutive proteolytic cleavages of the Notch receptor, S2 and S3, which results in the release of NICD (Guruharsha et al, 2012).…”
Section: /+mentioning
confidence: 99%
See 3 more Smart Citations